Analisis Seni Gambar Kaligrafi Santri Madrasah Aliyah Kelas XI Usia 16-17 Tahun di Pesantren Al Aulia Bogor Barat - Putri, Safira; Oetopo, Ataswarin (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
The purpose of this research is to analyze the art of calligraphy painting, as well as to find the meaning of each Qur'anic verse in the work and its implementation. It is based on the background of the fact that the factor in drawing calligraphy is more supportive of Qur'an reading and writing activities or can support the Qur'an tahfiz program and can be a material in preaching, improving the characteristics of santri / nun children to be better guided by the book of the Qur'an. The theories used for this research include Nasir's theory on the definition of religious institutions, Hakim's theory on the pesantren education model, Victor Lownfeld's "Creativity and Mental Growth", the developmental period of fine arts at the age of 16-17, Al-Faruqi's theory on reading the Quran and khat, and Susanto's theory on the definition of calligraphy. The method used is descriptive research with a qualitative approach. The type of analysis used is formalistic analysis using the theory according to Aliakbari and Hatami about "The Role of Calligraphy in Islamic Art and Its Interpretation", and content analysis using the theory according to Stokstad and Cothren and the theory of Sheila S. Blair and Jonathan M. Bloom. The results of this study indicate that there are several works of students who are still beginners in the technique of making calligraphic image decorations. The inhibiting factor in the implementation of extracurricular Al-Qur'an calligraphy at the Al-Aulia Islamic Boarding School is time constraints with other pesantren activities. The supporting factors are students, Islamic boarding school coaches, extracurricular advisors.The recommendation is the importance of improving and optimizing the creativity of students. For calligraphy extracurricular advisors, it is expected to utilize technological media, so that students are faster in the development of calligraphy knowledge and make references for further research related to the analysis of calligraphy drawing art in students.